Study on Salt and Water Balances at Segwa Drainage Pilot Area - Shrivastava, P K; Patel, B R (Journal of Agricultural Engineering, 2001)
Study has been conducted in 188 ha block at Segwa drainage pilot area to assess the impact of drainage on the removal of salts from the area. Pre drainage estimations were done to quantify the total salts deposited during 1996-97. Later post drainage estimation of salts left out during the year 1999-2000 was done based on field measurements. Equations on salt and water balance were formulated separately for pre and post drainage depending upon the available data. From the study, it was observed that during pre drainage period about 7 t/ha of salts remained as balance, whereas during post drainage period about 4.7 t/ha of salts remained as balance. Moreover this was the condition when only 11 % of the pilot area was brought under drainage.